2016
DOI: 10.1097/ijg.0000000000000166
|View full text |Cite
|
Sign up to set email alerts
|

Is There Any Role for the Choroid in Glaucoma?

Abstract: The choroid is part of the uveal tract and is a heavily vascularized bed that also contains connective tissue and melanin pigment. Given the role of the choroidal vasculature in the blood supply of the anterior laminar and prelaminar regions of the optic nerve head, the peripapillary choroid might be a relevant target for investigation in patients with glaucoma. The purpose of this paper is to critically review the current understanding of potential role of the choroid in the pathogenesis of glaucomatous damag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 123 publications
(137 reference statements)
0
21
0
1
Order By: Relevance
“…22,23 In addition, some studies have reported a lack of correlation between choroidal thickness and visual field defect 19,23,29,41,42 or retinal nerve fiber layer thickness. 19,25,33,34 As the real relationship between GON and choroidal thickness is not fully understood, 51 we present a detailed discussion to shed more light on the relationship between them and to try to explain why choroidal thickness of the macular and peripapillary regions is not significantly altered in OAG in comparison with that in the normal controls.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 In addition, some studies have reported a lack of correlation between choroidal thickness and visual field defect 19,23,29,41,42 or retinal nerve fiber layer thickness. 19,25,33,34 As the real relationship between GON and choroidal thickness is not fully understood, 51 we present a detailed discussion to shed more light on the relationship between them and to try to explain why choroidal thickness of the macular and peripapillary regions is not significantly altered in OAG in comparison with that in the normal controls.…”
Section: Discussionmentioning
confidence: 99%
“…The total number of people aged 40–80 years diagnosed as having primary open-angle glaucoma (POAG) is predicted to increase to 79.76 million in 2040, approximately 85% of the glaucomatous population [1]. The pathogenesis of open-angle glaucoma (OAG) has not been fully interpreted yet and accumulating evidence suggests that it is associated with the reduced blood perfusion to the optic nerve [24]. As the peripapillary choroid branches are the main source of blood supply to this region, it has been proposed that an abnormal choroid circulation could be involved in the occurrence of glaucomatous optic neuropathy.…”
Section: Introductionmentioning
confidence: 99%
“…of the blood flow within the eye, and is the major supplier of nutrients to the optic nerve head. Therefore, abnormal choroidal blood supply is considered a potential factor responsible for the development of glaucomatous optic neuropathy (5). Recent advancements in optical coherence tomography (OCT) technology have enabled researchers to detect choroidal changes more accurately (6).…”
Section: Introductionmentioning
confidence: 99%